c.3 - Gangrade, K. D (Delhi, 1974)
The social structure of a community is undoubtedly positively related to the degree of cooperation existing or possible in the village community. In every village community certain traditional ways of behaviour develop which determine to some extent whether the people will participate actively and cooperatively in community affairs, and determine almost completely the manner in which they will cooperate or resist. Most communities have practices which determine which groups will cooperate with certain other groups, on what kind of project, what particular way. Factions and the relationship between factions are probably factors which strongly influence community participation. Community and factional leaders appear to play an important role in determining the degree of India's community development and community participation. programme is unique ; its major objective is to get the parti- cipation of millions of persons and thousands of village groups. The present study is in the context of people's participation in rural community development programmes in India.
Keywords: Leadership